Penanganan Permukiman Kumuh Pulau Kambing Sungai Lakam Barat Kabupaten Karimun - Tesiherdawati; Asa Bintang Kapiarsa; Dina Fara Waidah; Tri Mardalena; Teguh Fringgodigdo (INDO PUBLISHING, 2025)
This study aims to analyze the characteristics and conditions of slum settlements in the Pulau Kambing area, Sungai Lakam Barat, Karimun Regency. Slum settlements are a major issue, particularly in urban areas, and are caused by various factors, including both physical and non-physical environmental conditions. These factors are important considerations in the implementation of slum management efforts. However, based on current conditions, many slum settlements remain unresolved, especially in terms of environmental, socio-economic, and cultural aspects. This research employs a qualitative method. The findings indicate that slum settlements in Pulau Kambing, Sungai Lakam Barat, Karimun Regency are predominantly characterized by substandard physical conditions, such as limited access to clean water and poor sanitation. Moreover, the public health level in the area tends to be low. Collaborative efforts between the government, communities, and relevant stakeholders are required to improve the condition of slum settlements in this region